STRATEGY FACTORS TO STRENGTHEN ACCESS TO MSME FINANCING THROUGH IOT INTEGRATION TO INCREASE COMPETITIVENESS: TOE FRAME APPROACH - Arbiya Magfiroh Rohmi; Sriyono Sriyono (Antis Publisher, 2026)
Objective: Access to financing is a critical factor for Micro, Small, and Medium Enterprises (MSMEs) to enhance business capacity and competitiveness; however, it remains a major challenge in Indonesia. This study aims to analyze the roles of technological, organizational, and environmental factors in strengthening access to financing and their implications for MSME competitiveness using the Technology–Organization–Environment (TOE) framework, with Internet of Things (IoT) integration as the technological context. Method: A quantitative research design was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The sample consisted of 109 food and beverage MSMEs in Sidoarjo Regency, selected through proportionate stratified sampling. Results: The results indicate that technological and organizational factors have a significant effect on MSME financing, while environmental factors do not show a significant direct effect. Furthermore, technology and organization significantly influence MSME competitiveness, whereas environmental factors are not significant determinants of competitiveness. The findings also reveal that financing has a significant negative effect on MSME competitiveness, suggesting that increased access to financing does not automatically enhance competitiveness unless it is managed productively and efficiently. Overall, the study highlights that strengthening MSME competitiveness is more effectively achieved through the development of internal capabilities, particularly technological readiness and organizational capacity, with financing acting as a supporting factor that must be strategically managed. Novelty: This study contributes empirically to the TOE literature by positioning IoT integration as a mechanism for improving operational data quality to support financing, access and competitiveness.